Host Adaptive Immune Status Regulates Expression of the Schistosome AMP-Activated Protein Kinase - Hunter, Kasandra S.; Davies, Stephen J. (Frontiers in Immunology, 2018)
Schistosomes exhibit profound developmental adaptations in response to the immune status of their mammalian host, including significant attenuation of parasite growth, development and reproduction in response to deficits in host adaptive immunity. These observations led us to hypothesize that schistosomes regulate the utilization of energy resources in response to immunological conditions within the host. To test this hypothesis, we identified and characterized the Schistosoma mansoni AMP-activated protein kinase (AMPK), a heterotrimeric enzyme complex that is central to regulating energy metabolism at the cellular and organismal level in eukaryotes. We show that expression of the catalytic α subunit is developmentally regulated during the parasite life cycle, with peak expression occurring in adult worms. However, the protein is present and phosphorylated in all life cycle stages examined, suggesting a need for active regulation of energy resources throughout the life cycle. In contrast, transcription of the AMPK α gene is down-regulated in cercariae and schistosomula, suggesting that the protein in these life cycle stages is pre-synthesized in the sporocyst and that expression must be re-initiated once inside the mammalian host. We also show that schistosome AMPK α activity in adult worms is sensitive to changes in the parasite’s environment, suggesting a mechanism by which schistosome metabolism may be responsive to host immune factors. Finally, we show that AMPK α expression is significantly down-regulated in parasites isolated from immunodeficient mice, suggesting that modulation of parasite energy metabolism may contribute to the attenuation of schistosome growth and reproduction in immunodeficient hosts. These findings provide insights into the molecular interactions between schistosomes and their vertebrate hosts and suggest that parasite energy metabolism may represent a novel target for anti-schistosome interventions.